2004
DOI: 10.1111/j.1399-0039.2004.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α‐308A allele, a possible severity risk factor of hemorrhagic manifestation in dengue fever patients

Abstract: Among the several hypothesis postulated to explain the pathogenesis of severe dengue disease, the model of immunopathogenesis is the most supported one with a likely important role played by the cascade of cytokines. This work describes single-nucleotide polymorphism of tumor necrosis factor (TNF)-alpha, interferon-gamma, interleukin (IL)-6, transforming growth factor-beta1, and IL-10 in patients with dengue virus infections and analyzes their relation with clinical manifestations of the disease. Because cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 18 publications
5
93
0
1
Order By: Relevance
“…Fernandez-Mestre et al [12], when studying the SNPs TNF -308 G>A, TGFB1 The frequency of the genotype IL6 -174 GC in the patients with DF presented by the authors was similar to the one found in our study (26.8% vs. 27.9%). However, the frequency of this genotype in controls was significantly lower than ours (21.7% vs 38.3% personal communication), possibly because of a difference in the racial components formation of the two populations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Fernandez-Mestre et al [12], when studying the SNPs TNF -308 G>A, TGFB1 The frequency of the genotype IL6 -174 GC in the patients with DF presented by the authors was similar to the one found in our study (26.8% vs. 27.9%). However, the frequency of this genotype in controls was significantly lower than ours (21.7% vs 38.3% personal communication), possibly because of a difference in the racial components formation of the two populations.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies show that immune response variations from polymorphisms *Address correspondence to this author at the Immunogenetics Lab, Clinical Analysis Department, Maringá State University, Maringá, Paraná, Brazil; E-mail: ramoliterno@uem.br and ramoliterno11@yahoo.com.br in regulatory regions of cytokine genes seem to influence the produced cytokine level and consequently the outbreak of different infectious disease, including Dengue Hemorrhagic Fever [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Host factors that increase the risk of severe dengue disease include female sex, several human leukocyte antigen (HLA) class I alleles, a promoter variant of the DC-SIGN receptor gene, a single-nucleotide polymorphism in the tumour necrosis factor (TNF) gene and AB blood group [31][32][33][34][35][36] . Host factors that reduce the risk of severe disease during a second dengue infection include race, second or third degree malnutrition, and polymorphisms in the Fcγ receptor and vitamin D receptor genes [37][38][39][40][41][42] .…”
Section: Dengue Virus Pathogenesismentioning
confidence: 99%
“…4). The ability of DV-immune In addition to high levels of viremia, cytokine cascades are thought to contribute to severe dengue disease (8,13,42). Induction of cytokine signaling was recently reported in postentry events of DV infection under ADE conditions in monocytic cell lines (7,33).…”
Section: Discussionmentioning
confidence: 99%